(untitled) (Colombia Medica, 1989)
Isolated splenic vein thrombosis is usually an obscure cause of upper gastrointestinal bleeding. The diagnosis should be suspected in every patient who presents variceal bleeding in the absence of signs of liver disease. Arteriography is essential for the diagnosis. Splenectomy is the treatment of choice for this localized type of portal hypertension.